New employee Copilot usage: Insights into productivity and socialization - Vorvoreanu, Mihaela; Graham, Sydney; Amy Heger; Dhanorkar, Shipi; Walker, Kathleen (Microsoft, 2025)
This report summarizes a mixed-methods study examining how a new generation of employees interacts with the generative AI assistant Microsoft Copilot for productivity when acclimating to a professional environment. Through a series of surveys, interviews, and a diary study, 125 Microsoft interns in a variety of roles provided insights into their usage and effects of Copilot in their new-employee roles. Top findings: We observed an association between frequency of Copilot use and workplace integration. Interns who used Copilot more frequently felt better socialized and identified with their teams more strongly. Greater usage of Copilot correlated with an increasingly favorable perception of the AI assistant. The most frequent and valued Copilot use cases were Information retrieval, writing assistance, and coding assistance. Participants highlighted multiple ways in which Copilot helped their productivity: (1) the benefit of seamless access to an AI assistant integrated across their work apps in the M365 suite; and Copilot capabilities that (2) helped new employees save time to focus on their primary responsibilities, (3) aided their getting “unstuck” on tasks, (4) stimulated creativity, and (5) served as a nonjudgmental assistant as they adapted to their new professional environment. Interns learned how to use Copilot by trial and error, picking up tips from peers, or accessing training documentation and resources. Cite as: Vorvoreanu, M., Graham, S., Heger, A., Dhanorkar, S., & Walker, K. (2025). New employee Copilot usage: Insights into productivity and socialization. Microsoft Technical Report MSR-TR-2025-24. https://www.microsoft.com/en-us/research/publication/new-employee-copilot-usage-insights-into-productivity-and-socialization/